Ventilation and Indoor Air Quality - Kumar, Ashok; Moreno Rangel, Alejandro; Khan, M. Amirul; Piasecki, Michał (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book focuses on the application of ventilation and indoor air quality (IAQ) in different settings, and is centred around different indoor environments and policymaking issues. It also explores how issues around health, IAQ and ventilation have evolved through the COVID-19 crisis. In connection with the growing need to determine and assess IAQ, new research seeks to test and investigate new methodologies based on research topics which include an increasing number of harmful substances and test methods. Ventilation and Indoor Air Quality ultimately aims to provide the reader with a comprehensive range of case studies, seeking to solve ventilation and IAQ issues from different perspectives. It presents 19 chapters related to regulations, homes, modelling, field studies, and technology related to ventilation and IAQ. Overall, this book provides state-of-the-art analysis and reviews so that readers with any level of prior knowledge of ventilation and IAQ are introduced to the latest research on these issues. This book was written to inspire and stimulate the development of further multidisciplinary research on IAQ issues.